Contemporary Trends of Research and Writing on Mosques Design: Analysis of The Most Recent Publications - Jawad Shakir Haraty, Hayder; Utaberta, Nangkula (International Journal of Engineering and Technology, 2019)
The reason of establishing the mosque was to introduce Islam to the people as it considered as a space of ritual and spiritual activates. In Islam, it is essentially to create a space that meet Muslims requirement from social to religious ones, the mosque is the place where all Muslims gathers to perform their Salat (prayer) and social aspects. Mosque is the Muslims establishment that act as a symbol and impetus of Islamic life, it represents the Muslims identity beside the main purpose of prayer and the social aspects. Historically, the mosque has undergone many changes since its first form, these changes led to the current architecture as it called an Islamic architecture which the mosque is representing the main element of it. The purpose of this study is to investigate in the most recent publication that have been discussing the architecture of the mosque in around the world. It also revealing what other researchers have commented about those mosques and their opinion. Several studies and publications have been intensely examined by reviewing the literature of numerous authors and focusing on the most recent studies (2015-2017) is the method of this paper. The findings from this review paper discovered that despite the many concerns mentioned in the researcher’s publications, there are still many gaps in the understanding of Islamic architecture and mosque’s layout. Further investigation needs to be started to fill out the existing failing of the literature to construct the idea of more Islamic architecture understanding.